Odpowiedzi

2010-03-07T13:07:06+01:00
X+2x= x+9
3x = x+9
3x-x= 9
2x = 9
x = 4,5

y+(2y-5) a gdzie reszta

3a+4=(a-1)+(a+7)
3a+4=a-1+a+7
3a+4=2a+6
3a-2a=6-4
a=2

(10-2b)+(6-b)=(10-b)+(4-b)
10-2b+6-b=10-b+4-b
16-3b=14-2b
16-14=3b-2b
2=b
Najlepsza Odpowiedź!
2010-03-07T13:09:28+01:00
A)
x+2x=x+9
3x-x=9
2x=9 |:2
x=4,5

b)
y+(2y-5)
y+2y-5
3y-5 <- to nie jest równanie

c)
3a+4=(a-1)+(a+7)
3a+4=a-1+a+7
3a+4=2a+6
a=2

d)
(10-2b)+(6-b)=(10-b)+(4-b)
10-2b+6-b=10-b+4-b
16-3b=14-2b
16-14=b
b=2


--------------------------------------------------------------------------
b)
y+(2y-5)=11-y
y+2y-5=11-y
3y-5=11-y
3y+y=11+5
4y=16 |:4
y=4

:)
2010-03-07T13:18:04+01:00
A
x + 2x = x + 9
x + 2x - x = 9
3x = 9
x = 9 : 3
x = 3

b
y + (2y - 5) = y + 2y -5 = 3y - 5

c
3a + 4 = (a - 1) + (a + 7)
3a + 4 = a - 1 + a + 7
3a - a - a = - 1 + 7 - 4
a = 2

d
(10 - 2b) + (6 - b) = (10 - b) + (4 - b)
10 - 2b + 6 - b = 10 - b + 4 - b
- 2b - b + b - b = 10 + 4 - 10 -6
- 3b = - 2
b = - 2 : (-3)
b = ⅔